Database Theory and Application, Bio-Science and Bio-Technology International Conferences, DTA and BSBT 2011, Held as Part of the Future Generation Information Technology Conference, FGIT 2001 in Conjunction with GDC 2011, Jeju Island, Korea, December 8-10, 2011. Proceedings - Kim, Tai-hoon.; Adeli, Hojjat; Cuzzocrea, Alfredo; Arslan, Tughrul; Zhang, Yanchun; Ma, Jianhua; Chung, Kyo-il.; Mariyam, Siti.; Song, Xiaofeng; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book comprises selected papers of the International Conferences, DTA and BSBT 2011, held as Part of the Future Generation Information Technology Conference, FGIT 2011, in Conjunction with GDC 2011, Jeju Island, Korea, in December 2011. The papers presented were carefully reviewed and selected from numerous submissions and focuse on the various aspects of database theory and application, and bio-science and bio-technology.
Keywords: Computer science; Computer software; Database management; Data mining; Information storage and retrieval systems; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Database Management; Information Storage and Retrieval; Information Systems Applications (incl. Internet).; Algorithm Analysis and Problem Complexity; Data Mining and Knowledge Discovery